Design and modeling of selective reinforcements for integral aircraft structures - Boscolo, Marco; Allegri, Giuliano; Zhang, Xiang (AIAA, 2008)
A numerical simulation is presented in this paper on the performance of crack retarders bonded to integral metallic structures. The work is described in two main parts. First, a novel modeling approach employing the finite element method has been developed for simulating the various failure mechanisms of a bonded structure and for predicting fatigue crack growth life. Crack growth in the substrate and the substrate/strap interface disbond failure are modeled in the framework of linear elastic fracture mechanics. A computer code interfacing with the commercial package MSC NASTRAN has been developed and validated by experimental tests. Second, the effectiveness of different strap configurations on crack growth retardation has been modeled; these include different strap materials, strap dimensions, and their locations on the substrate. The research has included two substrate materials and four strap materials, and at this stage the specimens were cured at room temperature. Strap stiffness and adhesive toughness are found to be the most influential parameters in designing crack retarders. A design tool has been developed based on the numerical simulation to achieve optimal crack retarder design in terms of prescribed fatigue life target and minimum structural weight added by the bonded reinforcement.